2022
DOI: 10.3390/ijms23020905
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Arthritis: Pathogenic Roles of Diverse Immune Cells

Abstract: Rheumatoid arthritis (RA) is a chronic, systemic autoimmune disease associated with synovial tissue proliferation, pannus formation, cartilage destruction, and systemic complications. Currently, advanced understandings of the pathologic mechanisms of autoreactive CD4+ T cells, B cells, macrophages, inflammatory cytokines, chemokines, and autoantibodies that cause RA have been achieved, despite the fact that much remains to be elucidated. This review provides an updated pathogenesis of RA which will unveil nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(123 citation statements)
references
References 134 publications
2
79
0
3
Order By: Relevance
“…Rheumatoid arthritis (RA) is an autoimmune disease characterized by joint inflammation, followed by cartilage destruction and bone erosion ( Jang et al, 2022 ). The study by Chen et al demonstrated that kefir peptides alleviated collagen-induced arthritis in the mouse models by inhibiting dendritic cells maturation and inflammatory cytokine release.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is an autoimmune disease characterized by joint inflammation, followed by cartilage destruction and bone erosion ( Jang et al, 2022 ). The study by Chen et al demonstrated that kefir peptides alleviated collagen-induced arthritis in the mouse models by inhibiting dendritic cells maturation and inflammatory cytokine release.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…From a genetic point of view there is a robust association between RA and HLA-DR4, a genetic anomaly, found in 70% of subjects affected by RA, of the human leukocyte antigen . Basically, in RA there is an aberrant inflammatory response to an unknown antigen andin which eventually leads to joint injury, induced by T-lymphocytes (CD4-CD8) that prime B-lymphocytes, which in turn differentiate into antibody-producing (Rheumatoid Factor, Polyclonal Antibodies) plasma cells, and activated macrophages which further sustain inflammation [20]. Systemic manifestations are due to the release of proinflammatory cytokines into the circulation, mainly represented by TNF-α, IL-6, IL-1 and IFNγ.…”
Section: Biomolecular Bases Of Immunopathogenesis In Ra and The Role ...mentioning
confidence: 99%
“…The most relevant innovation in the treatment of moderate-severe RA was the introduction in the therapeutic algorithm of TNF-α inhibitors [20]. TNF-α is produced usually by activated macrophages in the synovial membrane tissue in RA patients.…”
Section: Biomolecular Bases Of Immunopathogenesis In Ra and The Role ...mentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a chronic and systemic autoimmune disease. It is characterized by synovial inflammation that can lead to irreversible joint damage and disability when not managed 10 . Biomarkers of RA available for routine clinical use are rheumatoid factors (RF) and anti‐cyclic citrullinated peptides (CCP‐Ab).…”
Section: Introductionmentioning
confidence: 99%